Impact of SLCO1B1*5 on Flucloxacillin and Co-Amoxiclav–Related Liver Injury - Alshabeeb, Mohammad; Alomar, Fadhel A.; Khan, Amjad (Frontiers in Pharmacology, 2022)
Background: Idiosyncratic drug-induced liver injury (DILI) is a serious uncommon disease that may develop as a result of the intake of certain drugs such as the antimicrobials flucloxacillin and co-amoxiclav. The reported cases showed significant associations between DILI and various human leukocyte (HLA) markers. The solute carrier organic anion transporter 1B1 (SLCO1B1), a non-HLA candidate gene, was previously reported as a risk factor for liver injury induced by rifampin and methimazole. This study presumed that SLCO1B1 may play a general role in the DILI susceptibility and therefore investigated the association of rs4149056 (SLCO1B1*5, T521C) polymorphism with flucloxacillin- and co-amoxiclav–induced liver injury. Methodology: We recruited 155 and 165 DILI cases of white ancestral origin from various European countries but mainly from the United Kingdom owing to flucloxacillin and co-amoxiclav, respectively. Only adult patients (≥18 years) who were diagnosed with liver injury and who showed i) clinical jaundice or bilirubin >2x the upper limit of normal (ULN), ii) alanine aminotransferase (ALT) >5x ULN or iii) alkaline phosphatase (ALP) >2x ULN and bilirubin > ULN were selected. The population reference sample (POPRES), a European control group (n = 282), was used in comparison with the investigated cases. TaqMan SNP genotyping custom assay designed by Applied Biosystems was used to genotype both DILI cohorts for SLCO1B1 polymorphism (rs4149056). Allelic discrimination analysis was performed using a step one real-time PCR machine. Genotype differences between cases and controls were examined using Fisher’s exact test. GraphPad Prism version 5.0 was used to determine the p-value, odds ratio, and 95% confidence interval. Compliance of the control group with Hardy–Weinberg equilibrium was proven using a web-based calculator available at https://wpcalc.com/en/equilibrium-hardy-weinberg/. Results: A small number of cases failed genotyping in each cohort. Thus, only 149 flucloxacillin and 162 co-amoxiclav DILI cases were analyzed. Genotyping of both DILI cohorts did not show evidence of association with the variant rs4149056 (T521C) (OR = 0.71, 95% CI = 0.46–1.12; p = 0.17 for flucloxacillin cases and OR = 0.87, 95% CI = 0.56–1.33; p = 0.58 for co-amoxiclav), although slightly lower frequency (22.8%) of positive flucloxacillin cases was noticed than that of POPRES controls (29.4%). Conclusion: Carriage of the examined allele SLCO1B1*5 is not considered a risk factor for flucloxacillin DILI or co-amoxiclav DILI as presumed. Testing a different allele (SLCO1B1*1B) and another family member gene (SLCO1B3) may still be needed to provide a clearer role of SLCO1B drug transporters in DILI development–related to the chosen antimicrobials.